(b) Substitute i \( y=1 \), ii \( y=1.5 \) and iii \( y=2 \) into \( 4(2 y+3)-5 y<18-y \) to show that the solution set is correct.
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
First, let’s substitute \( y=1 \) into the inequality. We have \( 4(2(1)+3) - 5(1) < 18 - 1 \). This simplifies to \( 4(2+3) - 5 < 17 \), which becomes \( 4(5) - 5 < 17 \), or \( 20 - 5 < 17 \). Thus, \( 15 < 17 \) is true. Next, substituting \( y=1.5 \), we get \( 4(2(1.5)+3) - 5(1.5) < 18 - 1.5 \). This simplifies to \( 4(3+3) - 7.5 < 16.5 \), leading to \( 4(6) - 7.5 < 16.5 \), or \( 24 - 7.5 < 16.5 \). This results in \( 16.5 < 16.5 \), which is not true. Finally, substituting \( y=2 \), we find \( 4(2(2)+3) - 5(2) < 18 - 2 \). This evaluates to \( 4(4+3) - 10 < 16 \), simplifying to \( 4(7) - 10 < 16 \), or \( 28 - 10 < 16 \). Hence, \( 18 < 16 \) is false. The results confirm that the correct solution set is valid as \( y=1 \) satisfies the inequality, while \( y=1.5 \) and \( y=2 \) do not.